Assessing computational thinking practices and engagement - Škrobar, Jakob (CEPS journal, 2025)
Developing computational thinking in early primary education has gained increasing attention, with unplugged methods recognised as particularly effective for young learners. However, teachers' assessment of computational thinking, especially through process-oriented approaches, remains underexplored. The present study investigates how the participating Slovenian primary school teachers assessed computational thinking practices and students' engagement during an unplugged activity based on Bebras Challenge tasks. The results show that the teachers most frequently identified algorithmic thinking, pattern recognition and debugging, while decomposition and abstraction were observed less commonly. The activity received high ratings regarding the students' motivation and engagement, which several of the teachers attributed to the fact that it was conducted outdoors and involved physical movement. Collaboration and communication were also positively evaluated, although some teachers noted that competitiveness occasionally distracted the students. Overall, the findings support the feasibility of using process-oriented observation to assess computational thinking practices in unplugged settings, highlighting the need for targeted professional development to help teachers implement and assess computational thinking meaningfully. These insights contribute to the growing body of research on computational thinking assessment in primary education, underscoring the importance of providing teachers with structured support and context-specific tools.
Keywords: assessment; computational thinking; osnovna šola; primary school; računalniško mišljenje; računalništvo brez računalnika; STEM education; STEM-izobraževanje; unplugged; vrednotenje